Miejsce i rola języka kaszubskiego w systemie nauczania - Czaja, Michalina (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The aim of the article is to familiar with problems connected with intercultural aspects of transfer Kashubian language. There are taken under consideration not only transmissions of Kashubian language between generations, input teaching of Kashubian language at schools, schedule of teaching Kashubian language but also the educational situation Kashubian child in bilingual conditions. The article presents place and role of Kashubian language in educational system through family meaning, as a range balancing attempts to unify the state and to show that knowledge of the Kashubian strengthens family ties. With the introduction of the Kashubian language to schools it has a chance to survive and even growth.
Keywords: bilingualism; Kashubian culture; Kashubian language; Kashubian traditions; teaching Kashubian language